TLR2/caspase-5/Panx1 pathway mediates necrosis-induced NLRP3 inflammasome activation in macrophages during acute kidney injury - Chongbin Liu; Yanting Shen; Liuwei Huang; Jun Wang (Cell Death Discovery, 2022)
Abstract Acute kidney injury (AKI) is characterized by necroinflammation formed by necrotic tubular epithelial cells (TECs) and interstitial inflammation. In necroinflammation, macrophages are key inflammatory cells and can be activated and polarized into proinflammatory macrophages. Membranous Toll-like receptors (TLRs) can cooperate with intracellular NOD-like receptor protein 3 (NLRP3) to recognize danger signals from necrotic TECs and activate proinflammatory macrophages by assembling NLRP3 inflammasome. However, the cooperation between TLRs and NLRP3 is still unclear. Using conditioned medium from necrotic TECs, we confirmed that necrotic TECs could release danger signals to activate NLRP3 inflammasome in macrophages. We further identified that necrotic TECs-induced NLRP3 inflammasome activation was dependent on ATP secretion via Pannexin-1 (Panx1) channel in macrophages. Next, we verified that TLR2 was required for the activation of Panx1 and NLRP3 in macrophages. Mechanistically, we indicated that caspase-5 mediated TLR2-induced Panx1 activation. In addition, we showed that necrotic TECs-induced activation of TLR2/caspase-5/Panx1 axis could be decreased in macrophages when TECs was protected by N-acetylcysteine (NAC). Overall, we demonstrate that danger signals from necrotic TECs could activate NLRP3 inflammasome in macrophages via TLR2/caspase-5/Panx1 axis during AKI.